ANALISIS KADAR ALKOHOL PADA BALLO ASE (Oriza sativa) - Nur Qadri Rasyid; Hasnah Hasnah; Nurannisa Nurannisa; Muawanah Muawanah (Jurnal Medika, 2022)
Ballo is a traditional drink of palm wine originating from Bugis Makassar made through the fermentation process of sap, rice or fruit containing sugar. The results of fermentation produce alcohol consumed in the long term will cause cirrhosis of the liver. This study aims to determine the alcohol content contained in palm wine (ballo). This type of research was carried out by laboratory observation using the UV-Vis Spectrophotometer method. The object of this research is palm wine using 5 samples. The results of this study indicate that 5 samples contain alcohol content with sample A content of 18.67%, sample B of 28.42%, sample C of 30.67%, sample D of 8.17%, and sample E of 15.67 %. According to the regulation of the Minister of Health of the Republic of Indonesia NO. 86/MenKes/Per/VI/1997 concerning alcoholic beverages, it is explained that Group A drinks contain 1-5% ethanol content, Group B contains 5-20% ethanol content, and Group C contains 20-55% ethanol content. Based on the research that has been done, samples (A), (D) and (E) belong to group B drinks with moderate alcohol content, and samples (B) and (C) belong to group C with high alcohol content.